2012
DOI: 10.1016/j.nano.2011.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional nanoplatforms for fluorescence imaging and photodynamic therapy developed by post-loading photosensitizer and fluorophore to polyacrylamide nanoparticles

Abstract: We report a novel post-loading approach for constructing a multifunctional biodegradable polyacrylamide (PAA) nanoplatform for tumor-imaging (fluorescence) and photodynamic therapy (PDT). This approach provides an opportunity to post-load the imaging and therapeutic agents at desired concentrations. Among the PAA nanoparticles, a formulation containing the photosensitizer, HPPH [3-(1’-hexyloxyethyl)pyropheophorbide-a], and the cyanine dye in a ratio of 2:1 minimized the undesirable quenching of the HPPH electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 31 publications
0
44
0
Order By: Relevance
“…In general, two milliliters of the studied nanocarriers (with even or odd number of PE layers) were placed in a dialysis bag (Carl Roth, Germany, cut-off: 10 kDa) immersed in 30 ml phosphate buffered saline solution (PBS), pH $ 7.4 (control) or 1% HSA (Gupta et al, 2012;Opanasopit et al, 2005) dissolved in PBS. Analysis of the drug content in the released medium samples was performed using UV-Vis spectroscopy, by sampling the external solution at regular time intervals and replenishing with the same volume of fresh HSA or PBS.…”
Section: Release Kinetics Proceduresmentioning
confidence: 99%
“…In general, two milliliters of the studied nanocarriers (with even or odd number of PE layers) were placed in a dialysis bag (Carl Roth, Germany, cut-off: 10 kDa) immersed in 30 ml phosphate buffered saline solution (PBS), pH $ 7.4 (control) or 1% HSA (Gupta et al, 2012;Opanasopit et al, 2005) dissolved in PBS. Analysis of the drug content in the released medium samples was performed using UV-Vis spectroscopy, by sampling the external solution at regular time intervals and replenishing with the same volume of fresh HSA or PBS.…”
Section: Release Kinetics Proceduresmentioning
confidence: 99%
“…Gupta et al reported a new method to construct a multifunctional nanoplatform that could incorporate both the NR fluorophore and photosensitizer for NIRF imaging and photodynamic cancer therapy, making an ideal platform for simultaneous cancer imaging and therapy. 182 Karunakaran et al developed two hydrophilic porphyrins, THPP and Zn-THPP. In comparison with Photofrin, these probes have stronger intense fluorescence emission and singlet oxygen generation efficiency, showing the potential for PDT.…”
mentioning
confidence: 99%
“…UCNPs can be used to activates the photosensitizers in deep tissue because NIR light can penetrate a few centimeters into soft tissue due to weak absorption in the optical "transparent window". Four main classes of photosensitizers have been approved by the U.S. Food and Drug Administration for clinical use against cancer cells, containing porphyrin derivatives, chlorins, phthalocyanines, and porphycenes [100,101]. The second-generation photosensitizers of zinc (II)-phthalocyanine (ZnPc) have been proven highly selective for tumor targets and showed enhanced cytotoxic effects both in vitro and in vivo.…”
Section: Ucnps For Cancer Therapymentioning
confidence: 99%